Psychiatric Disorders in Complex Regional Pain Syndrome (CRPS): The Role of the Consultation-Liaison Psychiatrist - Michael Brinkers; Paulina Rumpelt; Anke Lux; Moritz Kretzschmar; Giselher Pfau (Pain Research and Management)
Background. Complex regional pain syndrome (CRPS) is a multifactorial disorder with complex aetiology and pathogenesis. At the outpatient pain clinic of Magdeburg University Hospital, all patients, without exception, are subject to permanent psychiatric care delivered by a consultation-liaison psychiatrist. In CRPS, psychological stabilization and treatment of the neuropathic aspects are equally important. The aim of this single-center retrospective study was to determine mental/psychiatric defects impairing pain processing at the time of investigation and show the effects of treating mental disorders and neuropathic pain with the same psychotropic drugs. Method. On admission, the consultation-liaison psychiatrist examined the mental state of every patient in a semistructured interview according to AMDP (working group for methods and documentation in psychiatry). Due to the model of the Department of Anaesthesiology, we are able to compare the group of CRPS patients with all other outpatients treated for pain. Results. The medical treatment of psychiatric dysfunction leads to an analgesic effect. Only every second CRPS patient had an additional psychiatric diagnosis, and 15.6% were diagnosed with depressive mood disorders and show a higher prevalence of depressive symptoms than the general population and exceed the mean for all patients treated in our pain clinic. Conclusions. In neuropathies, treatment of the neuropathic pain has a modulating effect on mental disorders. As CRPS patients are frequently affected by depressions, and owing to the connection between depression and suicidal tendencies, patients should be seen by a consultation-liaison psychiatrist, and nonpsychiatrists should pay special attention to this patient group.